Trichotomy, stability, and oscillation of a fuzzy difference equation - Stefanidou G; Papaschinopoulos G (Advances in Difference Equations, 2004)
We study the trichotomy character, the stability, and the oscillatory behavior of the positive solutions of a fuzzy difference equation.